On the Intertwining of Cellular Agriculture and Animal Agriculture: History, Materiality, Ideology, and Collaboration - Poirier, Nathan (Frontiers in Sustainable Food Systems, 2022)
This review essay documents continuities between (industrial) animal agriculture and cellular agriculture and raises key questions about whether or not the technology might be able to deliver on its promise of food system transformation. It traces how industrial history, connections to the livestock industry, and disavowal are extended through the innovation of cellular agriculture. In particular, it is shown that cellular agriculture has had connections to (industrial) animal agriculture since its very beginning and at nearly every step since then. I argue that cellular agriculture can be positioned as the epitome of (industrial) animal agriculture in terms of history, material practices, and ideology. Such a critique of cellular agriculture has become somewhat commonplace but while a number of papers have raised similar concerns individually, there exists no sustained focus on such similarities to make this point holistically. Such connections are important in framing the future of cellular agriculture and the fate of farmed animals and the environment. Carefully considering the continuities between cellular agriculture and animal agriculture is crucial when considering whether promoting cellular agricultural is a prudent approach to addressing problems associated with animal agriculture. The cumulative number and extent of connections covered in this essay leads to questions of who will benefit with the advent of cellular agriculture.